2007
DOI: 10.1080/03601230601017676
|View full text |Cite
|
Sign up to set email alerts
|

Emissions and distribution of methyl bromide in field beds applied at two rates and covered with two types of plastic mulches

Abstract: A field experiment was conducted to compare two plastic mulches and two application rates on surface emissions and subsurface distribution of methyl bromide (MBr) in field beds in Florida. Within 30 minutes after injection of MBr to 30 cm depth, MBr had diffused upward to soil surface in all beds covered with polyethylene film (PE) or virtually impermeable film (VIF) and applied at a high rate (392 kg/ha) and a low rate (196 kg/ha). Due to the highly permeable nature of PE, within 30 minutes after injection, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Films containing an EVOH barrier layer are currently referred to as TIF (Qin et al 2011). Films containing barrier polymers are significantly less permeable to fumigants than LDPE and high-density polyethylene (HDPE) mulches (Chellemi et al 2011; Gamliel et al 1998; Ou et al 2007; Qin et al 2011; Santos et al 2007; Wang et al 1998). Gamliel et al (1998) reported a 100-μm-thick LDPE film was more than 150-fold more permeable to methyl bromide than a 30-μm mulch containing an EVOH barrier layer.…”
mentioning
confidence: 99%
“…Films containing an EVOH barrier layer are currently referred to as TIF (Qin et al 2011). Films containing barrier polymers are significantly less permeable to fumigants than LDPE and high-density polyethylene (HDPE) mulches (Chellemi et al 2011; Gamliel et al 1998; Ou et al 2007; Qin et al 2011; Santos et al 2007; Wang et al 1998). Gamliel et al (1998) reported a 100-μm-thick LDPE film was more than 150-fold more permeable to methyl bromide than a 30-μm mulch containing an EVOH barrier layer.…”
mentioning
confidence: 99%
“…The most advanced highly retentive films are virtually impermeable film (VIF) and totally impermeable film (TIF). These films, manufactured by co-extrusion containing multilayers with barrier polymers, such as ethyl vinyl alcohol (EVOH) or polyamide (nylon), are significantly less permeable to fumigants than LDPE and HDPE (Chellemi et al 2011;Fennimore and Ajwa 2011;Gamliel et al 1998;Ou et al 2007;Qin et al 2011;Santos et al 2007b;Wang et al 1998;Yates et al 2002). Films containing an EVOH barrier layer are currently referred to as totally impermeable film (TIF) (Chow 2009;Fennimore and Ajwa 2011;Gao et al 2011;Qin et al 2011).…”
mentioning
confidence: 99%
“…Benefits of mulches with increased fumigant retention are a reduction in the amount of fumigant needed for effective pest control, lower emissions, and a decreased buffer zone requirement. Films manufactured by coextrusion containing multilayers with barrier polymers such as ethyl vinyl alcohol (EVOH) or polyamide (nylon) are significantly less permeable to fumigants (Gamliel et al, 1998;Ou et al, 2007;Santos et al, 2007;Wang et al, 1998;Yates et al, 2002) than LDPE and HDPE. These less permeable films were all classified as VIF in the literature regardless of the type of barrier material or permeability rate (Austerweil et al, 2006;Minuto et al, 1999;Ou et al, 2007;Wang et al, 1998;Yates et al, 2002).…”
mentioning
confidence: 99%